The motivational properties of emotions in foreign language learning - Méndez López, Mariza (Colombian Applied Linguistics Journal, 2011)
Although the process of learning a foreign language is replete with emotions, these have not been sufficiently studied in the field of English Language Teaching. The aim of this article is to report the motivational impact of the emotions experienced by second year students of an English Language Teaching programme in a South East Mexican University. Students were asked to keep an emotional journal for twelve weeks during their third term in order to map their emotions and their sources during instructed language learning. The results show that the emotions experienced most by students are: fear, happiness, worry, calm, sadness and excitement. Although there is a range of sources for emotional reactions, the five main sources of students’ emotions are: their insecurity about their speaking ability, the teachers’ attitudes, comparisons with peers, the classroom atmosphere, and the type of learning activities.The two main aspects identified as impacting on students’ motivation are: the teachers’ attitudes, and the classroom climate.